Data Data Everywhere; But Researchers Dare to Drink - Neil Seeman (ElectronicHealthcare, 2017)
[This article was originally published in Healthcare Quarterly, 15(2)] Data, data everywhere, yet nothing but a gripe. Gripe – characterized by academic chauvinism and pre-Internet era thinking – has been the chorus of some outspoken lawyers and ethicists, government officials and researchers who are terrified of the Big Brother of "Big Data" (Seeman 2012). To be fair, there are legitimate concerns about data mining, in particular the harnessing of data for secondary purposes to improve Canada's healthcare system. It is to this end that Colleen Flood, Canada research chair in health law and policy and editor of Data Data Everywhere, has assembled a sterling group of thought leaders to debate whether folks closer to my way of thinking ("data-access absolutists") or, on the other side (the camp I call the "data-access restrictionists") need to be more nuanced.
Keywords: Neil Seeman data mining Colleen Flood